MUSIK ANGKLUNG SEBAGAI MEDIA EKSPRESI BAGI PENDERITA TUNARUNGU DI SLB NEGERI SRAGEN (Jurnal Seni Musik, 2014)
Music can be accepted by all people include children with special needs. Therefore, the authors are interested in researching on " Angklung as Expression Media for Deaf People in Sragen Sragen Extraordinary School". The purpose of this study was to determine and describe (1) the learning process angklung music for people with hearing impairment in Sragen Extraordinary School, and (2) function of angklung as a medium of expression for people with hearing impairment in Sragen Extraordinary School. The study was conducted using descriptive qualitative methods because researchers will conduct the process of observing, identifying the object of research, data collection and data analysis, interpret according to its parts and describe. Based on research, the learning process is carried out through three phase, there are: (1) preparation; (2) implementation; and (3) performing. Teacher preparation phase to prepare learning materials, which are used angklung, learning media (light tone), grouping students and ensure students preparation. Implementation phase consists of two activities, (1) teach how to hold the angklung; and (2) teach how to play angklung covering â€œkrulungâ€ techniques, and teach the grade of tone. In the performing phase, teacher build students mentality by involve students perform in front of many people. Learning as a medium of expression is done through experience with performing that includes the aspects of the performing arts, the motion aspect, the aspect of voice, visual aspects, and aspects of the offender. Factors that influence the expression of the performing, the internal factors and external factors.